Exploring the Role of Video Games in Shaping Global South Narratives: A Study of Far Cry 2, Far Cry 3, and Mobile Legends hrough the Popular Culture and World Politics (PCWP) Framework - Rianto, Fathanaditya (Institute of International Studies, 2024)
In the current digital era, video games, which have evolved from ancient times, have become immensely popular media with significant impacts on society. In this context, it is evident that video games are not merely entertainment but also powerful instruments for conveying stories and ideologies, playing a significant role in communicating political and social messages. Through in-depth analysis of various game genres, this study explores how video games can reflect, influence, and even shape our perceptions of power dynamics, government policies, and global conflicts. This aligns with the framework of popular culture and world politics (PCWP), which views popular culture, including video games, as capable of influencing and shaping our perceptions of the Global South. This research also investigates how video games like “Far Cry 2”, “Far Cry 3”, and “Mobile Legends: Bang bang” can be used as tools to promote specific ideologies, both explicitly and implicitly. Employing a qualitative method with a case study approach to analyze narrative content formed within video games, this study, utilizing the PCWP framework, will examine how the stories presented in video games can shape understanding and attitudes toward social, economic, and political dynamics in the Global South.Keywords: video games; narratives; global south; popular culture; world politics